Вобраз маці ў творчасці Янкі Брыля - Alsztyniuk, Anna (Acta Polono-Ruthenica, 2018)
In the literary works of prominent Belarusian writer Yanka Bryl the on going theme is the subject of his mother. Through his own introspection and the collection of his life experiences, the writer talks about the character of his mother, her relationships with men, about death, and reaching the deeper meaning of life. The article examines the writer’s works in the book Птушкі і гнёзды, novel У сям’і, stories Разбуди меня завтра рано..., Сцежка-дарожка, Ты жывеш, За светлую памяць and also lyrical miniatures. Particular attention is paid to the development of the way Yanka Bryl shows and describes the individuality and persona of his Belarusian mother.